Degradation evaluation of high voltage insulating oils by terahertz spectroscopy - Chul Kim, Ki (International Journal of Engineering and Technology, 2018)
Background/Objectives: The stable electrical power supply is the most important issue for modern industrial society employing various electrical appliance. The power transformer is one of the most important component in the electrical power supply system.Methods/Statistical analysis: The common diagnosis method of insulating oil of transformer is gas-chromatograph. The gas-chromatograph is performed to detect dissolved gas ininsulating oil of transformerduring the stop-period of transformer unit. In this research, the optical properties of insulating oils of transformer (unused new oil, used oil of normal operation, and waste oil of malfunction) are analyzed using a terahertz time-domain spectroscopy in the range of 0.1 3.0 THz.Findings: The new insulating oil is colorless and transparent. The used insulating oil and waste insulating oil exhibit dark yellow and brown color. The THz sample pulses are delayed of phase and reduced of amplitude compare to passing through the free space. The reduce of amplitude is attributed to increasing of absorption due to aging effect of oils. The refractive index and absorption coefficient of insulating oils are calculated from measured THz pulses. The refractive index of â€˜new or used oilâ€™ exhibits a constant value of 1.455 and 1.463 in the full frequency range. But refractive index of â€˜waste oilâ€™ exhibits various values of 1.466 1.485 with the frequency, which is relatively high. The normalized amplitude of waste insulating oil is reduced. The absorption coefficient of waste insulating oil is increased linearly with the increase of frequency. The reducing of THz amplitude is attributed to increase of absorption due to aging effect of oils.Improvements/Applications: The aging effect of insulating oils of transformer is characterized by the portable THz-TDS system. It can be applied to in situ monitoring of insulating oil conditions.Â Â